Davis Addresses Chamber dinner; Sproule "Employee of the Year" - Eaton, Scott (Raton Range Raton, New Mexico, 1976)
Newspaper article on President of UNM Bud Davis addressing the Chamber of Commerce honoring City Clerk Eva Mae Sproule.
Master list item #: 3
File location is in the Raton file Cabinet
Keywords: Davis, Bud; Sproule, Eva Mae; Rikel, Elton; Bernard, Sonnny; Gurule, Robert; Mazzone, Mike; Monroe, John; Burrow, Ray; Popejoy, Tom; Lavander, Harold; Yaksich, George; Russell, Owen; Keeler, Curtis; Barnes, Clyde; Eagan, Ed; Burke, Larry; Hill, Paul; Vanlandingham; DiLisio, Joe Jr; Peryatel, Jack; Yob, Vince; Monroe, Aleene; Sawaya, Jehmiel; Roper, Jim; University of New Mexico; Chamber of Commerce; Sweet Shop; Erie Scientific; University of Colorado; U.S. Senate; Local History; Biography; Employee of the year; Banquat; Raton, New Mexico; Bernalillo; Albuquerque, New Mexico